A review of treatment of relapsing-remitting type of multiple sclerosis (RRMS) - Bydliński, Arkadiusz; Brożyna, Aleksandra; Małek, Natalia; Emerla, Sara; Kwiatkowska, Anita; Karłowicz, Konrad; Hermanowska, Maria; Lubomirska, Julia; Figurowska, Patrycja; Ciulkiewicz, Łukasz; et al. (Journal of Education, Health and Sport, 2024)
Introduction Multiple sclerosis (SM) is the most common chronic inflammatory-demyelinating disease of the Central Nervous System. In its course, a multifocal damage is done to a nervous tissue - myelin sheaths surrounding axons become disintegrated. This process leads to a dysfunction of the electrical impulses passage along nerve fibers which occurs as various symptoms that hinder the functioning of the patients. Aim of the study This review aims to summarize treatment methods of relapsing-remitting type of multiple sclerosis (RRMS). Following information will be presented: groups of medications, mechanism of its action, its most important side effects and its effectiveness. Material and method This review presents the current state of knowledge about relapsing-remitting type of multiple sclerosis (RRMS) treatment - it is based on Pubmed database and was carried out using keywords concerning the issues of multiple sclerosis. Cited articles were selected in order to base on up-to-date investigation results. Summary A wide range of therapeutic options let neurologists treat their patients accurately, but the basic knowledge about each substance should be assimilated to choose the best individual therapy. Patients suffering from multiple sclerosis differ from each other and a personal approach is needed to implement appropriate treatment as soon as possible. Early start allows patients to not to lose their everyday functioning areas, as the neurodegenerative process is stopped at the initial stage. If some changes in brain tissue structure are permanently done, neurologists should know the options of symptomatic treatment to alleviate a patient’s suffering.